Anaesthetic care for noma (cancrum oris) - the disease, the airway and how to provide anaesthetic care without a clinical safety infrastructure. (April 2020) - Braun, Ulrich; Wiese, Karl Günter; Merten, Hans-Albert; Timmermann, Arnd
Abstract: Noma (Cancrum oris) is an infectious acute disease that is prevalent in Africa, Asia and the American continent. This condition develops as a consequence of deficient nutrition. It is acquired by children between the ages of 1 and 7, and the children who contract it can die from sepsis within 2 weeks. The estimated mortality rate is in the range of 85%. The survivors have disfigurements of the face, massive scarring, open access to the oral and nasal cavities and trismus, which is the inability to open the mouth partially or completely. Noma, the neglected disease is observed among the poorest of the poor. The authors took part in a team effort to treat the sequelae of Noma in the year 2000 in Sokoto, Nigeria. There was no recovery room, intensive care unit, blood chemical laboratory, radiologic or advanced anaesthetic technology in the Noma Hospital in Sokoto as criteria of a clinical safety infrastructure. Flexible optical nasal intubation (FOI) was successful in all 65 Noma patients, where it was attempted. The nasal, cricothyroidotomy and tracheostomy routes in this disease are free, the oral access is obstructed. Supraglottic airways and oral tracheal intubation per conventional or video laryngoscopy are contraindicated. Highlights: Anaesthesia for the surgical treatment of facial disfigurements in Noma patients is only possible with a tracheal approach via the nasal FOI. Spontaneous ventilation is essential during the intubation procedure with FOI in Noma patients. An anaesthetic safety infrastructure may be missing in the hospitals of the continents, where Noma occurs.